(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The sinus lift is a procedure that is used frequently in oral surgery, different techniques exist to perform this procedure approaches, which allow the surgeon to give a sufficient bone height for planning a rehabilitative treatment with implant at the required site. In this case the unilateral lifting of the maxillary sinus floor by buccal bone window, with subsequent implant placement and lyophilized human bone in a single surgical procedure.